Oxidation of Sulphur Dioxide using Micro‐ and Nanoparticles of various Iron Oxides. Issue 15 (17th June 2021) - Reichelt, Lydia; Hippmann, Sebastian; Brichkin, Vyacheslav Nikolayevich; Bertau, Martin
Abstract: Sulphuric acid is the chemical with highest production rates in the world. At present, it is mainly synthesized using vanadium pentoxide as catalyst, which determines the applied production process particularly in terms of gas pre‐treatment and heat management. For processes, which cannot be run with vanadium pentoxide, alternative catalysts are required to make different SO2 qualities accessible to sulphuric acid production. Ferric oxides are a very promising alternative, since they combine higher thermal with improved chemical stability. Within this study, various ferric oxides were examined with regard to conversion rates and structural changes during application. Effects of crystal structure, particle size as well as thermal treatment and the influence of precipitation conditions were studied. Although conversion rates are very promising, it has become apparent, though, that these materials cannot compete with vanadium pentoxide in terms of conversion rate as well as long‐time stability, yet. Nevertheless, from the results of this study, it is clear that high potential lies in focused catalyst optimisation. Abstract :